Comparison of Efficacy and Safety of Third-Line Treatments for Advanced Gastric Cancer: A Systematic Review With Bayesian Network Meta-Analysis - Huang, Miao; Li, Jisheng; Yu, Xuejun; Xu, Qian; Zhang, Xue; Dai, Xin; Li, Song; Sheng, Lei; Huang, Kai; Liu, Lian (Frontiers in Oncology, 2021)
Background: Although various third-line treatments of advanced gastric cancer (AGC) significantly improved the overall survival, the optimal regimen has not been determined by now. This study aims to evaluate the efficacy and safety of multiple third-line treatments of AGC via integrated analysis and network meta-analysis (NMA) to provide valuable evidence for the optimal third-line systemic therapy for AGC. Methods: By searching the databases of PubMed, Embase and the Cochrane Central Register of Controlled Trials from Jan 01, 2005 to Dec 31, 2020, we included phase II/III randomized clinical trials (RCTs) of the third-line treatments for AGC to perform NMA. The main outcomes for NMA were median overall survival (mOS), median progression-free survival (mPFS), disease control rate (DCR) and adverse events (AEs). We also included phase IB/II non-RCTs and II/III RCTs of the third-line immune checkpoint inhibitors (ICIs) for integrated analysis for pooled mOS (POS), pooled mPFS (PPFS) and other outcomes. Results: Eight phase II/III RCTs and 2 ICIs-related phase IB/II non-RCTs were included for analysis, involving 9 treatment regimens and 3079 AGC patients. In terms of mOS, apatinib (hazard ratio [HR] 0.61, 95% credible interval [CrI] 0.48-0.78) and nivolumab (HR 0.62, 95% CrI 0.51-0.76) were the most effective treatments compared with placebo. Apatinib also significantly improved mPFS versus placebo (HR 0.38, 95% CrI 0.29-0.49). Nivolumab ranked first among all regimens for 1-year OS rate and achieved the best OS in patients with HER-2 positive tumor, patients with gastroesophageal junction (GEJ) cancer and patients without gastrectomy history. TAS-102 (OR 7.46, 95% CrI 4.61-12.51) was the most toxic treatment in terms of AEs of grade 3 and higher (≥3 AEs). Pembrolizumab was more likely to cause immune related adverse event. Finally, the POS, pooled 1-year OS rate, pooled ORR and PPFS of AGC patients treated with third-line ICIs were 5.1 months, 25%, 10% and 1.71 months respectively. Conclusions: Apatinib and nivolumab are the most effective treatments for the third-line treatment of AGC in contrast to the third-line chemotherapy. For AGC patients with HER-2 positive tumor, patients with GEJ cancer and patients without gastrectomy history, ICIs could be the optimal third-line treatment choice.